2021
DOI: 10.1111/njb.03026
|View full text |Cite
|
Sign up to set email alerts
|

Competitors and ruderals go to town: plant community composition and function along an urbanisation gradient

Abstract: Urbanisation is expected to function as a filter for plant species by changing the physiochemical environment, causing species turnover along an urbanisation gradient. Analyses of the functional traits of species characteristic of different urbanisation levels allow for comparisons across studies, irrespective of exact species composition. This study aims to examine how plant species and functional traits vary with urbanisation. An independent dataset obtained through the Global Biodiversity Information Facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Anthropogenic change, including urbanisation, alters the composition of ecological communities (Kampichler et al 2012;Petersen et al 2021;Wang et al 2017;Dale 2018). As environmental conditions become more suitable for some species and less suitable for others, we observe community turnover along environmental gradients (Legendre and Caceres 2013;Dunson and Travis 1991).…”
Section: Introductionmentioning
confidence: 84%
“…Anthropogenic change, including urbanisation, alters the composition of ecological communities (Kampichler et al 2012;Petersen et al 2021;Wang et al 2017;Dale 2018). As environmental conditions become more suitable for some species and less suitable for others, we observe community turnover along environmental gradients (Legendre and Caceres 2013;Dunson and Travis 1991).…”
Section: Introductionmentioning
confidence: 84%
“…The findings of our study offer a novel perspective, suggesting that the association between traits facilitating larger plant and leaf sizes may have also undergone evolutionary changes in urban situations. However, the adaptive significance of the plant-leaf size correlation in urban conditions remains unclear (Petersen et al 2021). Therefore, future studies using transplant experiments with fitness measurements should be conducted to investigate this relationship (cf., Gorton et al 2018).…”
Section: Urban-specific Trait Correlationsmentioning
confidence: 99%
“…2019; Petersen et al . 2021). Urban plant populations often have larger sizes in order to acquire more carbon for reproductive traits than rural populations (Lambrecht et al .…”
Section: Introductionmentioning
confidence: 99%
“…The municipality is well-sampled with regards to species occurrence records, in part due to the presence and activity of a university and a University Museum. Birds are particularly well-registered (Petersen et al 2020(Petersen et al , 2021a.…”
Section: Study Areamentioning
confidence: 99%
“…It has been shown that land-cover and land-use determine species richness differently among different taxa, groups of conservation concern, and functional groups (Petersen et al 2020(Petersen et al , 2021a. In addition to differences in species richness, land-cover affects community composition; changes in landcover are thus likely to cause species turnover.…”
Section: Introductionmentioning
confidence: 99%